Utilização da metodologia análise PM para solução de problema - Bochnia, André Luis (2012)
This paper has the aim of applying PM Analysis in a real industry case wich causes line shutdown in the extruder. The adopted methodology classifies the research as applied with the discussion of results in a qualitive way. The work was developed in a company in packing area, in a city of Ponta Grossa, wich has developed the concept of Total Productive Maintenance since 1999. This helps the development of an appropriated environment for a continuous improving. It is exactly in a mature environment like this where the PM analysis tool should be adopted in order to solve chronicle losses. This growing need of continuous improvement is motivated by the market competition, that has been more and more severe with companies that do not adapt in to this current scenario. Towards this necessity one of the forms the companies found out to keep being competitive is through the reduction of production total cost, which is obtained for instance (in such company) in a line shuting down reduction this matter will be this paper object of study.